Substance abuse : information for school counselors, social workers, therapists, and counselors - Fisher, Gary L.; Harrison, Thomas C. (Boston : Pearson/Allyn and Bacon, 2005)
Writing specifically for students who intend to practice in generalist settings, Fisher and Harrison, both affiliated with the University of Nebraska, combine clinical examples with research to provide students in counseling, psychology, and social work with a detailed overview of the alcohol and drug field.
Includes bibliographical references and index.
Keywords: Social work with drug addicts -- United States; Social work with alcoholics -- United States; Drug addicts -- United States. -- Counseling